"Mechanisms of democratic erosion: Analysing populist rhetoric across international contexts" - Logu, Klajdi (International Journal of Innovative Research and Scientific Studies, 2025)
This paper explores how populist rhetoric contributes to the erosion of democratic trust by analyzing the emotional and polarizing strategies employed by populist leaders in various international contexts. It aims to reveal the mechanisms through which such rhetoric undermines core democratic values and institutions. The research adopts a qualitative content analysis of political speeches delivered by prominent populist leaders from Hungary, the USA, India, Turkey, and France. Using NVivo software, thematic patterns were extracted and coded to identify rhetorical strategies. Supplementary computational analysis was conducted through Doc2Vec modeling to detect semantic patterns and quantify linguistic commonalities. The study finds that populist rhetoric consistently frames political discourse as a binary struggle between “the people” and “the elite,” reinforced through emotional appeals, simplification of complex issues, and narratives of victimhood. These rhetorical tools foster public skepticism, weaken trust in democratic institutions such as the judiciary and media, and exacerbate social polarization. Populist rhetoric poses a significant challenge to democratic stability. By delegitimizing institutional authority and amplifying antagonistic narratives, populist leaders undermine the very foundations of democratic governance. The findings highlight the need for strengthening institutional transparency, civic education, and media literacy as tools to resist populist manipulation. Policymakers and democratic stakeholders must proactively counteract these narratives to protect democratic norms and foster social cohesion.